Pembentukan Kultur Konsumtif melalui eWOM Kuliner di Instagram - Lailia Hifziati (Universitas Muhammadiyah Yogyakarta, 2017)
Communication eWOM as culinary promotion media has grown rapidly in Instagram, with Food Instagrammer followers who actively become opinion seeker and the shaper of the phenomenon itself. In addition to being the most up-to-date eWOM culinary promotional tool in Instagram has formed a consumptive culture. This research is to see how followers food Instagrammer able to play an active role in forming culinary eWOM and consumptive culture in Instagram. This study uses virtual ethnography, which focuses on media object analysis taken from three active followers of Instagrammer professional food. The results of this study indicate that culinary eWOM in Instagram besides establishing a new identity becomes an effective promotional tool rather than the use of other media. eWOM culinary in instagram is able to form millennial consumer culture in the digital era.